KAJIAN KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMK DI KABUPATEN BANDUNG BARAT PADA MATERI PROGRAM LINEAR - Yuliani, Devi; Nurhasanah, Nurhasanah; Rohaeti, Euis Eti (Al-Khawarizmi, 2018)
This research aims to examine students' mathematical communication abilities on linear program subject. The research method is using descriptive research with qualitative approach. The subjects who is selected in this research is 5 students of 11th Grade from vocational school in West Bandung regency. The instrument of this research is in the form of test and interview. The result of the research is mathematic communication ability of 11th Grade vocational school students in West Bandung regency in understanding linear program subject is still low. Conclusion of this research is students effort of daily events in language or mathematical symbols or composing a mathematical model of an event in question 1 of 35.0%, students effort in painting or presenting real objects, drawings, and diagrams in the form of ideas and or mathematical symbols at number 2 of 30.0%, and the students effort in explaining ideas, situations and mathematical relationships, both orally and in writing using real objects, images, graphs and algebraic expressions in question 3 of 45.0%. Abstract english version, written using Time New Roman-12, italic. Abstract contain research aim/purpose, method, and reseach results; written in 1 paragraph, single space among rows, using past tense sentences.